Case study of the Saujana Aromatica Spa and Beauty: Market growth a quest to achieve sustainable enterprise - Sukri, Suriani; Mohd Yusuf, Bibi Noraini; Mansor, Mohd Fitri; Kamil, Syahida (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2013)
This case examines the impact of the internal and external environment on enterprise business specifically on spa and beauty business. Financial, human and technical constraints appeared to be a major setback for these companies to grow and expand. Ineffective joint venture and lack of effective marketing plan further worsen the company’s earnings as the losses occurred due to poor resources management and limited sources of earning which is mainly from spa service and sales commission.The aim of the case is to emphasis on issues faced by the spa and beauty business specifically registered under enterprise status.